2015
DOI: 10.1039/c5ra12251a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cage-like nano-CaCO3 hollow spheres for enhanced CO2 sorption

Abstract: Cage-like nano-CaCO 3 hollow spheres with different cavity diameters for CO 2 sorption were prepared using the template-directed synthesis method. Carbon sphere templates with different diameters were synthesized via a hydrothermal reaction of starch under variable conditions. Field emission scanning electron microscopy (SEM) and transmission electron microscope (TEM) images indicated that the synthesized cage-like nano-CaCO 3 hollow spheres had different cavity diameters of 0.52 µm, 1.62 µm and 2.93 µm. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Moreover, the presence of highly porous shells would allow rapid transport of CO2 to and from the material. 39,45,46 It should also be noted that the shells are composed of CaO and CuO (or CaO, CuO and calcium copper oxide) nano-sized particles, among which CaO nanoparticles minimize the diffusion distance of CO2 through the freshly formed CaCO3 product layer in the diffusion-controlled stage during the carbonation reaction. 44 Furthermore, the three-dimensional hollow microsphere structures realize a physical separation of the nanoparticles, which is expected to effectively mitigate particle/grain agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the presence of highly porous shells would allow rapid transport of CO2 to and from the material. 39,45,46 It should also be noted that the shells are composed of CaO and CuO (or CaO, CuO and calcium copper oxide) nano-sized particles, among which CaO nanoparticles minimize the diffusion distance of CO2 through the freshly formed CaCO3 product layer in the diffusion-controlled stage during the carbonation reaction. 44 Furthermore, the three-dimensional hollow microsphere structures realize a physical separation of the nanoparticles, which is expected to effectively mitigate particle/grain agglomeration.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon based template is one of the most commonly used for the synthesis of structured CaO sorbents. Ping et al 69 found that the cage-like CaCO 3 hollow spheres synthesised using Ca(NO 3 ) 2 , urea and polysaccharide spheres template showed an excellent CO 2 uptake of up to 78.6 wt.% (100.2 mol%) in the first cycle, 45 wt.% higher than the same composition synthesised without the template. Colloidal carbon spheres derived from glucose were used as the template for the synthesis of CaO/CaZrO 3 and CaO sorbents.…”
Section: Effect Of Synthesis Parametersmentioning
confidence: 99%
“…Lastly, the equilibrium constants of reactions, K bSMR and K gSMR could be determined according to eqn (27) and 28, respectively.…”
Section: Computational Uid Dynamicsmentioning
confidence: 99%
“…The CO 2 capacity, rate of CO 2 caption, and stability of these sorbents are important properties to increase the performance of SESRE. 3,9,11,13,19,[24][25][26][27] The advantages of natural CaO sorbents, such as dolomite and limestone, are that they are inexpensive, easy to nd, and have higher CO 2 capacity than other sorbents. However, CaO sorbents have lower thermal cyclic stability than the other sorbents.…”
Section: Introductionmentioning
confidence: 99%